Histology and molecular pathology of iliotibial tract contracture in patients with gluteal muscle contracture. Issue 9 (20th September 2019) - Yuan, Bang-tuo; Qu, Feng; Wang, Shao-xia; Qi, Wei; Shen, Xue-zhen; Li, Chun-bao; Liu, Yu-jie
Abstract : The present study aimed to examine the pathologic changes of the iliotibial tract and discusses its relationship with gluteal muscle contracture. Samples of contractual iliotibial tracts were collected from six patients with contractures of the gluteal muscles and iliotibial tracts during their surgical treatment. Samples of normal iliotibial tracts were collected from six patients receiving surgeries for avascular necrosis of the femoral head who had no contractures of the gluteal muscles and iliotibial tracts. The tissue samples were stained using Hematoxylin and Eosin (H&E), Masson's trichrome, and Sirius Red. The mRNA and protein levels of various tissue repair genes were determined using quantitative real-time PCR and Western blotting. Both the normal and contractual iliotibial tracts consisted of type I and III collagens. The contractual iliotibial tracts had a significantly higher proportion of type III collagen in comparison with the normal iliotibial tracts. The mRNA expression levels and protein levels of tissue repair genes TGFβ 1, bFGF, and matrix metalloproteinase-1 (MMP-1) in the contractual iliotibial tracts were up-regulated in comparison with that in the normal iliotibial tracts. However, the mRNA expression levels and protein levels of tissue inhibitors of metalloproteinase-1 (TIMP) in the contractual iliotibial tracts were down-regulated in comparison with that in the normal iliotibial tracts. The contractures of both the gluteal muscles and the iliotibial tracts share similar histology and molecular pathology. Our results indicate that iliotibial tract contracture is secondary to the gluteal muscle contracture and is a constant tissue repair process.